Evaluation of the responses of institutions and actors to the 2015/2016 El Niño drought in the Komati catchment in Southern Africa: lessons to support future drought management - Sifundza, LS; van der Zaag, P; Masih, I (Water SA, 2019)
Future climate projections for Southern Africa indicate an increase in the severity of droughts. Drought preparedness and management are important in such regions to minimise impacts on people and the environment. The aim of this study was to explore the responses of different institutions and actors to the 2015/2016 drought in the Komati catchment, and, consequently, what these experiences imply for drought management in the future. This was done through in-depth interviews with 30 key actors in the study area, including farmers, engineers, water managers and weather services personnel. Additionally, we examined data on precipitation, streamflows, reservoir levels, publications and communications in media, and minutes of the Komati Joint Operation Forum (KJOF) meetings. The results indicate that, whereas scientific tools for water resources management and drought forecasting exist in the catchment, the information generated using the tools was not sufficiently utilised in water (re) allocation decision making. This can be explained by the indifference of many stakeholders to early warning information, and by the preference of stakeholders to secure farm water supplies to minimize socio-economic losses in the short term. This resulted in late implementation of drought measures, when the drought had already started. Most of the measures implemented (i.e. water rationing and intensified monitoring) only helped partially in the crisis situation and did not tackle the root causes of vulnerability of the water users, especially for farmers. From the 2015/2016 drought we learnt that pro-active drought management could be supported through developing a drought management plan that is endorsed by all actors. More efforts are needed to improve how weather forecast information is packaged, communicated, deliberated and used by institutions (e.g. KJOF) and end-users (e.g. farmers). Moreover, this case study demonstrates that learning from past drought events is useful for improving evidence-based tools, policies and practices for drought management.